МАНЖ АЛБАН БИЧГИИН ХҮНДЭТГЭЛ ИЛЭРХИЙЛЭХ ЁСНООС - Э.Мөнх-учрал, (Acta Mongolica, 2010)
This paper is related to the writing culture of the Manchu’s. There are lots of work done on the history, language and culture of the Manchu’s from various angles and perspectives; however, these works are lacking studies on document formatting culture. Under document processing one can observe essential characteristics of writing culture: addressing, content, formulation ...etc. Moreover, it's available to follow utensils that are used in writing like paper quality, brush, ink, color and many other qualities. In addition to this, the receiver of document can judge what level of respect is shown to him. All above mentioned qualities can appear only if this culture of document processing is highly developed. Within the frame of this paper, a standard of writings in different respect forms represented in Manchu archival documents is discussed, taking the example of Manchu Emperor, who was a supreme person of the state. The main focus is based on three points: forms of writings, content of documents and rituals applied to these documents. Within the scope of writing forms the followings are studied: word positioning, assiduous applications for writings and used stationaries (paper, color, seal and etc). The content considers respect forms in language style. The rituals are related to a particular ceremony of Manchu imperial documents. Once Taizong has said that the Manchu state has been developed according to the tradition of the four states: Dai Liao, Jin, Sung and Dai Yuan. Similarly, the Manchu document processing which was written in both Manchu and Mongolian languages are blossomed on the basis of the Mongolian writing tradition exercised for longer period of the history. During the historical development, the Manchu state has been originated from just a small guardian unit called Jianzhou which gradually extended to the territory that covered Manjuur, China Proper, Mongolia and Tibet.